Factors related to the students' involvement in selected organizations: the case of Adamson University. - Santos, Rosario B. (Animo Repository, 1995)
This study investigates the factors hypothesized to be correlated with the students in selected school organizations in Adamson University. These factors, predicted to be person-related, were the needs for affiliation and achievement. Those which were parent-related were composed of both the parents' education and occupation. Those which were organization-related included the availability and openness of the adviser of the organization. Eighty-seven officers and members of selected organizations belonging to the 19-23 age bracket of students on the last two years of college were surveyed. This sample was taken from a population of 1,500 students who represented 29 academic and socio-civic organizations of the six colleges of Adamson University. The respondents answered a questionnaire eliciting data on personal, familial, and organizational concerns. The Edwards Personal Preference Schedule, a personality inventory, measured their need for achievement and affiliation. The data were quantified and statistically tested using the Statistical Package for Social Sciences (SPSS). The statistical results showed that the time availability of the adviser was the sole factor that was positively and significantly correlated with the students' involvement in the organization. A certain inaccuracy in the measurement of this variable, however, raised the possibility that the results could be more statistical than actual. Discussion of the findings, taken within the context of the case under investigation, pointed out the importance of the organizations' advisers. This dealt particularly with the amount of time they devoted to the organization. It is recommended that greater coordination be done by the Guidance Office in achieving further student development. The Office of the Student Pastoral Services should assist in the formulation and implementation of training programs for the faculty advisers of the different organizations.